1975
DOI: 10.1121/1.2002192
|View full text |Cite
|
Sign up to set email alerts
|

Critical bandwidth in lateralization: Effect of level

Abstract: The onset-time difference ΔT needed to lateralize 30-msec dichotic tone bursts toward the leading ear was measured as a function of the frequency difference ΔF between the burst in one ear and the burst in the other ear. An adaptive procedure (a variation of BUDTIF) was used to concentrate judgments in the vicinity of 75% correct. Signal frequencies were centered at a geometric mean of 2000 or 6000 Hz. The level in the right ear was set near 25, 50, or 80 dB SPL. At each of the three reference SPLs, all tone b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A number of previous studies have shown that normal listeners are able to lateralize signals on the basis of interaural differences even when the signals differ in spectral content at the two ears (B6k6sy, 1963;Deatherage, 1961;Harris, 1960;Henning, 1974;Perrott and Williams, 1970;Thurlow and Elfner, 1959;Zerlin, 1969;Zurek and Leshowitz, 1975). Moreover, when the stimuli are amplitude-modulated tones (Nuetzel and Hafter, 1981) or tone bursts (Scharf, 1974;Scharf et al, 1976), the onset-time difference required to lateralize toward the leading ear A Tis nearly independent of the frequency difference AFbetween the two ears provided the tones are in the same critical band; however, beyond the critical bandwidth, A T increases with AF. The critical bandwidth measured in the lateralization of tone bursts centered on 0.5 kHz corresponds closely to the approximately 100-Hz bandwidth that several investigators have used to interpret binaural masking level differences at 0.25 and 0.5 kHz (Webster, 1951;Lang-ford and Jeffress, 1964; Rabiner, 1964;Sondhi, 1965).…”
Section: Introductionmentioning
confidence: 95%
“…A number of previous studies have shown that normal listeners are able to lateralize signals on the basis of interaural differences even when the signals differ in spectral content at the two ears (B6k6sy, 1963;Deatherage, 1961;Harris, 1960;Henning, 1974;Perrott and Williams, 1970;Thurlow and Elfner, 1959;Zerlin, 1969;Zurek and Leshowitz, 1975). Moreover, when the stimuli are amplitude-modulated tones (Nuetzel and Hafter, 1981) or tone bursts (Scharf, 1974;Scharf et al, 1976), the onset-time difference required to lateralize toward the leading ear A Tis nearly independent of the frequency difference AFbetween the two ears provided the tones are in the same critical band; however, beyond the critical bandwidth, A T increases with AF. The critical bandwidth measured in the lateralization of tone bursts centered on 0.5 kHz corresponds closely to the approximately 100-Hz bandwidth that several investigators have used to interpret binaural masking level differences at 0.25 and 0.5 kHz (Webster, 1951;Lang-ford and Jeffress, 1964; Rabiner, 1964;Sondhi, 1965).…”
Section: Introductionmentioning
confidence: 95%
“…In pure tone signals, ITD is processed up to 1500 Hz, referred to as fine-structure ITD (ITD FS ) (Brughera et al, 2013;Delphi et al, 2017;Verschooten et al, 2019). In complex sounds, ITD at higher frequencies (beyond 1500 Hz) is perceived through the difference in the sound's envelope timing, known as envelope ITD (ITD ENV ) (Yost, 2017); and transient onset ITD cues, which refer to the difference in the arrival time of the sound to the perceiver's different ears (ITD ONSET ) (Scharf et al, 1976).…”
Section: Introductionmentioning
confidence: 99%